1979
DOI: 10.1051/jphyscol:1979335
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependent Pitch in Cholesteric Phase

Abstract: Rksum6.-On ktudie thkoriquement les phases ordonnkes des cristaux liquides cholestkriques en considkrant l'interaction molkculaire comme la somme d'un terme rkpulsif entre les bPtonnets chiraux rigides et de termes dispersifs attractifs de Maier-Saupe et Goossens. La mkthode de symktrie briske est appliquke pour calculer 1'Cnergie libre en fonction du parametre d'ordre et du pas de la structure hklicoTdale. On calcule la tempkrature de clarification et le pas dkpendant des parametres du champ intermolCculaire.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…For example, the theory proposed by Kimura et al . [ 3 ] predicts a linear dependence of the reciprocal pitch against ϕ(1 – ϕ/3)/(1 – ϕ) 2 , where ϕ is the polymer concentration, which is in fairly good agreement with the experiments [ 4 ]. Due to cellulose relatively stiff cellulose backbone, which forces a parallel orientation of the chains, a wide range of cellulose derivatives was found to form both lyotropic and thermotropic chiral nematic liquid crystals [ 5 ].…”
Section: Introductionsupporting
confidence: 80%
“…For example, the theory proposed by Kimura et al . [ 3 ] predicts a linear dependence of the reciprocal pitch against ϕ(1 – ϕ/3)/(1 – ϕ) 2 , where ϕ is the polymer concentration, which is in fairly good agreement with the experiments [ 4 ]. Due to cellulose relatively stiff cellulose backbone, which forces a parallel orientation of the chains, a wide range of cellulose derivatives was found to form both lyotropic and thermotropic chiral nematic liquid crystals [ 5 ].…”
Section: Introductionsupporting
confidence: 80%
“…The side chains assume the helical arrangement forced by the helical conformation of the main chain, produce a screw-like van der Waals surface on the exterior of main-chain backbone, and cause the twist by their steric interaction. Kimura et al considered the temperature dependence of cholesteric pitch by a coupling of these two effects and showed that the twisting power, q = 2π/P , is given by the following equation [26,27]:…”
Section: Discussionmentioning
confidence: 99%
“…51 This entropic contribution affects the temperature dependence of a cholesteric pitch. 43 The theory can be extended to nematic and cholesteric liquid crystal mixtures, binary mixtures of cholesteric liquid crystals, cholesteric liquid crystalline polymers, and lyotropic cholesteric phases.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] To describe cholesteric phases, the chiral dispersion intermolecular interactions have been treated by many authors. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] The configuration of the constituent ith molecule is characterized by its position vector r i and its orientation vector i . It has been shown that the intermolecular chiral interaction is given by the term ( 1 × 2 •r 12 )P 1 ( 1 • 2 ) in the lowest order, wherer 12 = (r 1 − r 2 )/|r 1 − r 2 |.…”
Section: Introductionmentioning
confidence: 99%